(untitled) (El Hilo de la Fabula, 2023)
The aim of this article is to depict the most innovative aspects of the lectures presented in the XXIII Congress of the ICLA that was held in July 2022 in Tbilisi, Georgia. The information is assembled by subject and is focused on theoretical aspects applied to the analysis of all literary spectrums: literature as science, literary texts and translation.